AN INNOVATIVE APPROACH OF MATERIAL FLOW SYSTEM FOR MOTION REDUCTION IN A CAST MANUFACTURING FIRM - Shafee, N.A.Q.M.; Mohamad, E.; Rahman, M.S.A.; Rahman, A.A.; Ito, T. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
A door hardware manufacturing company in Melaka, Malaysia has faced challenges with an inefficient material handling system due to unnecessary operator movements in the sub-assembly processing line. This study aims to address this issue by proposing an innovative material flow system focused on three main stations: Manual Piston Assembly (MPA), Cushion Back Check (CBC), and Spring Adjustment Screw (SAS). The new material flow system is developed using Spaghetti Diagram (SD) and Line Balancing (LB), leading to improved operator movement and the reorganization of workstations and storage areas. Consequently, the distance between the storage area and CBC/MPA has been reduced by 88%, from 36.2 meters to 4.4 meters, and from SAS, it has been reduced by 72%, from 18.7 meters to 5.30 meters. This significant reduction has minimized worker motion and eliminated unnecessary movements. Overall, this study demonstrates that LB is an effective method for addressing bottlenecks and optimizing the material flow system in this cast manufacturing firm.